PENGARUH STRATEGI PEMBELAJARAN INDEX CARD MATCH TERHADAP AKTIVITAS BELAJAR SISWA PADA MATERI GERAK PADA TUMBUHAN - Umi Rodiyah; Fitri Oviyanti; Yustina Hapida (Bioilmi: Jurnal Pendidikan, 2018)
This study aims to determine the effect of learning strategy Index Card Match on student learning activities on the material plants movement system in VIII class. Subjects in this study came from 2 classes include VIII.1 and VIII. 2 The research method used in this research is quasi experimental design method with Pretest-Posttest Control Group Design Design. Sampling technique is using non probability sampling technique. Instrument that is used in this research is observation sheet to measure student activity, the test to measure student learning result as supporting data. The result of this research shows that there is influence of student activity using index card match strategy. This can be seen in the students' learning activity in the experimental class at 72%, while the control class 55%. In the second meeting in the experimental class was increased by 82%, while the control class was 66%. The average value of post test in the experimental class is 85,31 while the mean posttest of the control class is 73,57.